2019
DOI: 10.1371/journal.pone.0218944
|View full text |Cite
|
Sign up to set email alerts
|

CC chemokine CCL1 receptor CCR8 mediates conversion of mesenchymal stem cells to embryoid bodies expressing FOXP3+CCR8+ regulatory T cells

Abstract: Embryoid bodies (EBs) are three dimensional aggregates of pluripotent stem cells primarily used to investigate morphogenesis and cell toxicity, are also attractive tools in regenerative medicine. While embryonic stem cells (ESCs) and induced pluripotent cells (IPSCs) have been shown to form EBs in mouse, primate and humans, EB formation have not been previously demonstrated in mesenchymal stem cells (MSCs). Here we show that rat MSCs form EBs; which express regulatory T cell (Treg) marker Foxp3 and CC chemokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Accordingly, CCR8 knockout mice show impaired Th2 cytokine production, and the CCL1/CCR8 axis has been implicated in the cutaneous homing of T cells (51, 52). Studies have shown that CCL1 and its receptor, CCR8, mediate the conversion of mesenchymal stem cells to embryoid bodies expressing Treg cells (53), and disruption of the CCL1-CCR8 axis inhibits vascular Treg recruitment and functions (54). In the present study, we found that M2b macrophage exosomes carrying the CCL1 protein to the colon interact with CCR8 to promote IL-4 expression (Th2 polarization) and increase Treg percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, CCR8 knockout mice show impaired Th2 cytokine production, and the CCL1/CCR8 axis has been implicated in the cutaneous homing of T cells (51, 52). Studies have shown that CCL1 and its receptor, CCR8, mediate the conversion of mesenchymal stem cells to embryoid bodies expressing Treg cells (53), and disruption of the CCL1-CCR8 axis inhibits vascular Treg recruitment and functions (54). In the present study, we found that M2b macrophage exosomes carrying the CCL1 protein to the colon interact with CCR8 to promote IL-4 expression (Th2 polarization) and increase Treg percentages.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that this species may utilize its virulence for multiple tasks depending on the stage/state of development of the atherosclerotic plaque. Clonal hematopoiesis of intermediate potential is a known risk factor in tumor pathology and has recently been shown to be higher in individuals with atherosclerosis (45,46). Variation in host stem cells (due to aging, disease) may influence differential immune response to pathogenic bacteria at the site of injury which may influence the mediation of symptomatic vs. asymptomatic atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%